Effects of Anaerobic Fatigue on Biomechanical Variable Changes in Softball Batting Techniques (Universitas Pendidikan Indonesia, 2024)
Softball is a sport that requires a good coordination between physical and technical aspects. Anaerobic fatigue can be a factor affecting the execution of softball batting techniques. However, an in-depth understanding of the impact of anaerobic fatigue on biomechanical variables in the batting technique context is still under-explored. This study aimed to identify and analyze the effect of anaerobic fatigue on changes in biomechanical variables in softball batting techniques. The purpose of this study was to evaluate how anaerobic fatigue affects key biomechanical variables in softball batting techniques. This information is expected to provide additional insight into the importance of anaerobic fitness in improving the performance of softball athletes. This study used experimental method with a pretest-posttest design. The subjects were experienced softball players selected using purposive sampling. Anaerobic fatigue was induced using a high-intensity training protocol. The biomechanical variables measured included bat swing speed, swing angle, and shot precision. Measurements were taken before and after the training. Data were analyzed using a paired t-test to examine significant changes. The study showed that anaerobic fatigue had a significant effect on key biomechanical variables in softball batting techniques. There was a significant decrease in bat swing speed and batting precision after anaerobic fatigue. The average bat swing speed before fatigue was 3.60 m/s, which decreased to 2.14 m/s after fatigue. In addition, the swing angle and batting precision also showed significant changes, with a lower left knee angle approaching the ground in the pre-fatigue group. This study found empirical evidence supporting the effect of anaerobic fatigue on biomechanical variables in softball batting technique. These results provide an important contribution to the general understanding of the relationship between anaerobic fatigue and technical performance in softball. Therefore, athlete trainings and preparations need to pay attention to anaerobic fitness aspects to maintain optimal performance during the game.